Solanaceous Vegetable in Temperate region of Arunachal Pradesh – A Production Cost Analysis - Tiwari, A. K. (Indian Journal of Hill Farming, 2018)
Temperate region are the areas of hilly terrain where vegetable farming are really tough, and most of the people do it for their subsistence, although the farming of solanaceous vegetable is done in these areas but only for there household needs, so, it is important for an agricultural person that he should know the production cost of these vegetable for commercial production, and with much pressure on land holdings, limited resource availability with farmers and increased cost of agricultural inputs, it has become imperative for farmers to make optimum use of their resources for realizing maximum farm returns, it was observed that farmers were spending maximum budget of total cost of production on human labor, indicating the effort needed for the adoption of farm mechanization. Therefore, there is an urgent need of changing farmers attitude from traditional to adoption of improved production practices through various means of transfer of technologies for enhancing total production of the country.